Analisis Rubrik Penilaian Keterampilan Berpikir Kritis Berbasis ESD di Kelas Tinggi Sekolah Dasar - Nadia Nahariy Saffanah; Ghullam Hamdu (JUDIKA (JURNAL PENDIDIKAN UNSIKA), 2022)
Abstract ESD is an alternative in the world of education that is expected to direct students in realizing a sustainable life. Critical thinking competencies are one of the eight key ESD competencies that must be developed through esd-based skills assessment rubrics. This study aims to analyze the skill assessment rubric associated with ESD-based critical thinking competencies. The research using is a qualitative method with descriptive. The subjects of this study were 6 teachers in high grade in Garut and Tasikmalaya districts. The research data was carried out through interview method and documentation studies of the rubrics that had been used by the teacher. The results of this study indicate that there are 3 esd areas that are in accordance with the 2013 curriculum, it can be seen if in the rubric that the researchers analyzed there are 50% rubrics covering social, economic, and environmental. However, in the context of critical thinking, only 25% of rubrics used critical thinking indicators in assessing the skills of learners. Teachers find it difficult to use and develop skills assessment rubrics. The development of ESD-based critical thinking skills rubric will be effective and important to facilitate teachers in conducting skills assessments. Keywords: ESD, assessment rubric, critical thinking, skill assessment